Lithium ion battery silicon-carbon composite negative electrode material and preparation method and application thereof
By adopting a rigid three-dimensional porous carbon skeleton and a coordinated domain-limiting structure of elastic carbon and nano-silicon in lithium-ion batteries, the problems of volume expansion/shrinkage of silicon-carbon composite anode materials for lithium-ion batteries during charging and discharging are solved, and battery performance with high specific capacity and long life is achieved.
Patent Information
- Application Number
- CN202510000020.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-01
- Publication Date
- 2025-04-11
AI Technical Summary
The existing lithium-ion battery silicon-carbon composite anode materials have problems such as volume expansion/shrinkage, particle crushing and instability of solid electrolyte interfaces during charging and discharging, resulting in insufficient cycle stability and structural integrity.
The rigid three-dimensional porous carbon framework and the coordinated domain structure of elastic carbon and nanosilicon are adopted to buffer the volume changes of nanosilicon through the three-dimensional pore structure to ensure the electrochemical cycle stability and structural integrity of the material.
It improves the charging specific capacity, discharge specific capacity and cycle stability of lithium-ion batteries, extends the battery life, and enhances the structural integrity.
Smart Images

Figure CN119812271A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium ion batteries, and specifically relates to a lithium ion battery silicon-carbon composite negative electrode material and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries have abundant lithium resources, low cost and reliable safety, and have great potential in the next generation of energy storage devices. In recent years, various negative electrode materials have emerged. For example: Si, Sn, Ge, Zn, P and Sn, Si, Ge-based oxides, while graphite is usually used as a commercial negative electrode material in lithium-ion batteries. However, graphite has a low theoretical specific capacity of 372 mAh g -1 In comparison, the theoretical specific capacity of Si is 4200 mAh g -1 It has become a hot topic in research and is the preferred negative electrode material for high-energy lithium-ion batteries. However, Si undergoes a huge volume expansion change (more than 300%) during the charge and discharge process. The crushing and non-uniform volume change of Si particles cause the solid electrolyte interface (SEI) layer to grow continuously during the charge / discharge process, and the active material is lost. The solid electrolyte interface has poor contact and becomes unstable, which leads to low coulomb efficiency, rapid capacity decay, and poor cycle stability. For example, the resistance between particles is high, the surface area is too large, and the density is too low. These problems can be solved by constructing nanoscale structures within micron-sized particles. At the same time, many structures have been proposed to eliminate these problems, such as designing core-shell structures, yolk-eggshell structures, 3D porous structures, embedded structures, and nanowire silicon-carbon composite materials. Although these rationally designed silicon-carbon composite structures can be used to alleviate the volume expansion problem, further improving the stability and structural integrity of silicon-carbon composite negative electrode materials relative to silicon-carbon composite negative electrode materials is a long-term problem that needs to be solved. Especially for silicon-carbon lithium-ion battery negative electrode materials with high volumetric capacity and low volume expansion rate, they need to undergo structural evolution such as volume expansion / contraction, particle breakage, and SEI film instability during the charging and discharging process.
[0003] The Chinese patent document with publication number CN118800893A discloses a lithium-ion battery silicon-carbon negative electrode material and its preparation method. With highly conductive graphene as the substrate, a SiNPs@graphene@C silicon-carbon composite material with a "sandwich" structure is prepared by combining mechanical molding and wet method to promote the formation of a stable SEI film, maintain the structural integrity of the electrode material, improve the conductivity and improve the overall performance of the SiNPs@graphene@C silicon-carbon composite material. However, at a current density of 0.1C, its charge capacity is 692.8mAh g -1 , needs to be improved.
[0004] A Chinese patent document with publication number CN118763172A discloses a silicon-carbon negative electrode with a three-dimensional conductive network, a preparation method and an application thereof. The silicon-carbon negative electrode composite negative electrode material with a three-dimensional conductive network is prepared by a sol-gel method. The experimental operation is complicated, and the Co element and methylimidazole will cause environmental pollution, which is not conducive to widespread application.
[0005] Therefore, the development of lithium-ion battery silicon-based negative electrode materials with excellent cycle stability and structural integrity is of great significance to promote the industrial application of lithium-ion batteries. However, the existing technology still needs to be improved and enhanced. Summary of the invention
[0006] In view of the deficiencies of the prior art, the purpose of the present invention is to provide a lithium-ion battery silicon-carbon composite negative electrode material, which is composed of a rigid three-dimensional porous carbon skeleton and elastic carbon and nano-silicon uniformly filled in the rigid three-dimensional porous carbon skeleton. The elastic carbon filled in the pore structure of the rigid three-dimensional porous carbon skeleton can buffer the volume expansion / contraction of nano-silicon during the lithium insertion / extraction process, ensuring that the material has excellent electrochemical cycle stability; the rigid three-dimensional porous carbon skeleton confines the volume strain of elastic carbon and nano-silicon in the three-dimensional pore structure, so that the lithium-ion battery silicon-carbon composite negative electrode material has excellent structural integrity.
[0007] Another object of the present invention is to provide a method for preparing the above-mentioned lithium-ion battery silicon-carbon composite negative electrode material.
[0008] Another object of the present invention is to provide application of the above-mentioned lithium-ion battery silicon-carbon composite negative electrode material in lithium-ion batteries.
[0009] The purpose of the present invention is achieved through the following technical solutions.
[0010] A lithium-ion battery silicon-carbon composite negative electrode material comprises: a rigid three-dimensional porous carbon skeleton, elastic carbon and nano-silicon, wherein the rigid three-dimensional porous carbon skeleton is formed with three-dimensional pores, and the elastic carbon and nano-silicon are filled in the three-dimensional pores formed by the rigid three-dimensional porous carbon skeleton, the rigid three-dimensional porous carbon skeleton is obtained by carbonizing polyurethane foam having a through three-dimensional porous structure, and the elastic carbon is obtained by carbonizing a carbon source, and the carbon source is citric acid or chitosan. In terms of mass fraction, the ratio of polyurethane foam, carbon source and nano-silicon is (1-3):(0.5-1):1.
[0011] In the above technical solution, the pore size of the rigid three-dimensional porous carbon skeleton is ≤1 micron.
[0012] A method for preparing a lithium-ion battery silicon-carbon composite negative electrode material comprises the following steps:
[0013] Step 1, ball-milling polyurethane foam into particles with a particle size of 5 to 15 microns, dispersing the granular polyurethane foam, carbon source and nano silicon (powder) in a solvent, and mixing until uniform to obtain a first dispersion, wherein the ratio of the granular polyurethane foam, carbon source and nano silicon is (1 to 3): (0.5 to 1): 1 by mass;
[0014] In step 1, the ratio of nano silicon to solvent is 1:(20-33) by mass.
[0015] In step 1, the solvent is anhydrous ethanol.
[0016] Step 2: Dry the first dispersion to obtain a precursor material, calcine the precursor material at 600-800° C. for 2-4 hours in an inert gas atmosphere, and cool it in the furnace to obtain a lithium-ion battery silicon-carbon composite negative electrode material.
[0017] In the above technical solution, the pore size of the polyurethane foam is ≤1 micron.
[0018] In the above technical solution, the particle size of nano silicon (powder) is ≤100 nanometers.
[0019] The application of the above lithium-ion battery silicon-carbon composite negative electrode material in improving the charging specific capacity, discharging specific capacity and / or capacity retention rate of the lithium-ion battery.
[0020] A lithium-ion battery comprises a lithium-ion battery silicon-carbon composite negative electrode material.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] The present invention uses bionic honeycomb structure silicon carbon as the basic framework, wherein the rigid three-dimensional porous carbon skeleton has a three-dimensional through-hole structure of submicron scale, and the pore structure is filled with elastic carbon and nano silicon. Through the synergistic confinement effect of the rigid three-dimensional carbon skeleton and the elastic carbon, the volume expansion / contraction problem of the nano silicon can be buffered, and the elastic carbon will not be broken due to the volume change of the nano silicon. In addition, the rigid three-dimensional porous carbon skeleton restricts the elastic deformation of the carbon to occur in the three-dimensional holes, so that the lithium ion battery prepared by the present invention has the advantages of high specific capacity, long life (cycle stability), etc., and has potential application prospects in high specific energy lithium ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 XRD patterns of the silicon-carbon composite negative electrode materials for lithium-ion batteries prepared in Examples 1 to 6;
[0024] FIG2 is a SEM of the silicon-carbon composite negative electrode material for lithium-ion batteries prepared in Examples 1 to 6, wherein: Figure 2(a) to Figure 2(f) The SEM images of the lithium-ion battery silicon-carbon composite negative electrode materials prepared in Examples 1 to 6 are shown in sequence;
[0025] Figure 3 The lithium ion batteries of Examples 7 to 12 are 0.2Ag -1 The charge and discharge curve diagram below;
[0026] Figure 4 The lithium ion batteries of Examples 7 to 12 are 1Ag -1 Cycle performance diagram below;
[0027] Figure 5 XRD spectra of the lithium ion battery silicon-carbon composite negative electrode material prepared in Comparative Examples 1 and 2 and the negative electrode material of Comparative Example 3;
[0028] Figure 6 The lithium ion batteries of Comparative Examples 4 to 6 are 0.2Ag -1 The charge and discharge curve diagram below;
[0029] Figure 7 The lithium ion batteries of Comparative Examples 4 to 6 are 1Ag -1 The cycle performance diagram below. DETAILED DESCRIPTION
[0030] The technical solution of the present invention is further described below in conjunction with specific embodiments.
[0031] The raw material information involved in the following examples is as follows:
[0032]
[0033]
[0034] The various performance indicators in the following examples are strictly measured using precise instruments or standard test methods:
[0035] The XRD patterns were measured by an X-ray diffractometer (ARL EQUINOX 3000, Thermo Fisher Scientific) at 40 kV and 40 mA in the 2θ range of 10 to 100°.
[0036] The surface morphology of the material was characterized by using a Quanta FEG 250 field emission scanning electron microscope and a Verios 460L ultra-high resolution field emission scanning electron microscope from FEI Company of the United States.
[0037] On the LAND system (LAND CT2001A, China), at 0.01–1.5 V (vs. Li / Li + ) potential window for constant current charge and discharge measurements and cycle performance tests.
[0038] The nano silicon (powder) used in the following examples and comparative examples is the same.
[0039] 1Ag -1 =0.24C.
[0040] Examples 1 to 6
[0041] A lithium-ion battery silicon-carbon composite negative electrode material comprises: a rigid three-dimensional porous carbon skeleton, elastic carbon and nano-silicon, wherein the rigid three-dimensional porous carbon skeleton forms three-dimensional pores, and the elastic carbon and nano-silicon are filled in the three-dimensional pores formed by the rigid three-dimensional porous carbon skeleton, the rigid three-dimensional porous carbon skeleton is obtained by carbonizing a polyurethane foam having a through three-dimensional porous structure, and the elastic carbon is obtained by carbonizing a carbon source (the carbon source is citric acid).
[0042] The method for preparing the above-mentioned lithium-ion battery silicon-carbon composite negative electrode material comprises the following steps:
[0043] Step 1, ball-milling blocky polyurethane foam into particles with a particle size of 5 to 15 microns (pore size of polyurethane foam ≤ 1 micron), dispersing granular polyurethane foam, carbon source and nano silicon (powder) (particle size of nano silicon powder ≤ 100 nanometers) in a solvent, ultrasonically cleaning at a frequency of 40000 Hz for 25 minutes in an ultrasonic cleaning machine, and then stirring at a speed of 600 rpm for 6 hours in a magnetic stirrer at 83°C until uniform, to obtain a first dispersion, wherein the ratio of granular polyurethane foam, carbon source and nano silicon (powder) is X by mass, and the ratio of nano silicon (powder) to solvent is 1:20 by mass, and the solvent is anhydrous ethanol;
[0044] Step 2: Dry the first dispersion in a vacuum oven at 80°C for 12 hours to obtain a precursor material, transfer the precursor material to a tubular furnace, heat it to 600°C at a rate of 5°C / min under an argon protective atmosphere, and calcine it at 600°C for 2 hours. Cool it in the furnace to obtain a silicon-carbon composite negative electrode material for a lithium-ion battery.
[0045] The X values are shown in Table 1.
[0046] Table 1
[0047] Silicon-carbon composite negative electrode materials for lithium-ion batteries X Example 1 1:0.5:1 Example 2 1:1:1 Example 3 3:1:1 Example 4 3:0.5:1 Example 5 2:0.5:1 Example 6 2:1:1
[0048] Comparative Example 1
[0049] A method for preparing a lithium-ion battery silicon-carbon composite negative electrode material comprises the following steps:
[0050] Step 1, dispersing citric acid and nano silicon (powder) in anhydrous ethanol, ultrasonically cleaning at a frequency of 40000 Hz for 25 minutes in an ultrasonic cleaning machine, stirring at a speed of 600 rpm for 6 hours in a magnetic stirrer at 83°C until uniform, and drying in a vacuum oven at 80°C for 12 hours to obtain substance A, wherein the ratio of citric acid to nano silicon (powder) is 1:1 by mass, and the ratio of nano silicon (powder) to anhydrous ethanol is 1:20 by mass;
[0051] Step 2, transfer material A to a tubular furnace, raise the temperature to 800°C at a rate of 5°C / min under an argon protective atmosphere, and calcine at 800°C for 2h, and cool with the furnace to obtain a lithium-ion battery silicon-carbon composite negative electrode material.
[0052] Comparative Example 2
[0053] A method for preparing a lithium-ion battery silicon-carbon composite negative electrode material comprises the following steps:
[0054] Step 1, ball-milling blocky polyurethane foam into particles of 5-15 microns (pore diameter of polyurethane foam ≤ 1 micron), dispersing granular polyurethane foam and nano silicon (powder) in anhydrous ethanol, ultrasonically cleaning at a frequency of 40000 Hz for 25 minutes in an ultrasonic cleaning machine, stirring at a speed of 600 rpm for 6 hours in a magnetic stirrer at 83°C until uniform, and drying in a vacuum oven at 80°C for 12 hours to obtain substance B, wherein the ratio of granular polyurethane foam to nano silicon (powder) is 2:1 by mass, and the ratio of nano silicon (powder) to anhydrous ethanol is 1:20 by mass;
[0055] Step 2, transfer substance B to a tubular furnace, raise the temperature to 800°C at a rate of 5°C / min under an argon protective atmosphere, and calcine at 800°C for 4 hours, and cool with the furnace to obtain a lithium-ion battery silicon-carbon composite negative electrode material.
[0056] Comparative Example 3
[0057] A negative electrode material, which is nano silicon (powder).
[0058] Examples 7 to 12 and Comparative Examples 4 to 6
[0059] A method for preparing a lithium-ion battery comprises: in a glove box, assembling a positive electrode shell, a pole piece, a diaphragm, a lithium sheet, a gasket, and a negative electrode shell in order to obtain a lithium-ion battery, wherein the electrolyte in the electrolyte used is LiPF6 (the concentration of the electrolyte is 1M, and the model of the electrolyte is LB-048), and the diaphragm is a Celgard 2325PP film. The method for obtaining the pole piece is: mixing a negative electrode material, a conductive agent (acetylene black) and a binder solution (the binder solution is a mixture of sodium carboxymethyl cellulose (CMCNa), polyacrylic acid and deionized water, and the concentration of sodium carboxymethyl cellulose (CMCNa) in the binder solution is 15 mg mL -1 The concentration of polyacrylic acid in the binder solution is 15 mg mL -1 , by mass fraction, the ratio of the negative electrode material, the conductive agent, the sodium carboxymethyl cellulose (CMCNa) in the binder solution and the polyacrylic acid in the binder solution is 7:2:0.5:0.5), put it into an agate mortar and grind it for 30 minutes until it is uniform, and obtain a slurry. The slurry is evenly coated on the copper foil as the current collector with a scraper, and dried in a vacuum oven at 80°C for 12 hours to fully volatilize the deionized water. When the temperature drops to room temperature, take it out, cut out a circular electrode sheet with a diameter of 12mm with a sheet cutter, and then use a sheet press to press the circular electrode sheet at a pressure of 10MPa for 30s to obtain a pole sheet with a diameter of 12mm (the negative electrode material loading on the pole sheet with a diameter of 12mm is 1-1.3mg). The negative electrode material is one of the lithium ion battery silicon-carbon composite negative electrode materials prepared in Examples 1 to 6 and Comparative Examples 1 to 3.
[0060] Table 2
[0061] Lithium-ion battery Preparation of negative electrode materials for lithium-ion batteries Example 7 Example 1 Example 8 Example 2 Example 9 Example 3 Example 10 Example 4 Embodiment 11 Example 5 Example 12 Example 6 Comparative Example 4 Comparative Example 1 Comparative Example 5 Comparative Example 2 Comparative Example 6 Comparative Example 3
[0062] The XRD patterns of the silicon-carbon composite negative electrode materials for lithium-ion batteries prepared in Examples 1 to 6 are shown in FIG. Figure 1 As shown, after XRD analysis, Figure 1 The diffraction peak intensity of the lithium ion battery silicon-carbon composite negative electrode material prepared in Examples 1 to 6 is relatively high, indicating that it has good crystallinity, which is indistinguishable from the standard card PDF#27-1402, and has the characteristic peak of crystalline Si of the cubic system, indicating that the lithium ion battery silicon-carbon composite negative electrode material prepared in Examples 1 to 6 is a crystalline Si phase.
[0063] The SEM image of the lithium ion battery silicon-carbon composite negative electrode material prepared in Example 1 is shown in Figure 2(a), the SEM image of the lithium ion battery silicon-carbon composite negative electrode material prepared in Example 2 is shown in Figure 2(b), the SEM image of the lithium ion battery silicon-carbon composite negative electrode material prepared in Example 3 is shown in Figure 2(c), the SEM image of the lithium ion battery silicon-carbon composite negative electrode material prepared in Example 4 is shown in Figure 2(d), the SEM image of the lithium ion battery silicon-carbon composite negative electrode material prepared in Example 5 is shown in Figure 2(e), and the SEM image of the lithium ion battery silicon-carbon composite negative electrode material prepared in Example 6 is shown in Figure 2(f). The lithium ion battery silicon-carbon composite negative electrode materials prepared in Examples 1 to 6 are typical honeycomb structures with relatively uniform particle size distribution.
[0064] The charge and discharge curves of the lithium-ion battery prepared from the lithium-ion battery silicon-carbon composite negative electrode materials of Examples 1 to 6 are shown in FIG. Figure 3 As shown, at 0.01–1.5V, 0.2Ag -1 The specific charging capacity of the lithium-ion battery prepared by the lithium-ion battery silicon-carbon composite negative electrode material of Example 1 is 1762.37 mAh g -1 The specific charging capacity of the lithium-ion battery prepared by the lithium-ion battery silicon-carbon composite negative electrode material of Example 2 is 2583.59 mAh g -1 The specific charging capacity of the lithium-ion battery prepared by the lithium-ion battery silicon-carbon composite negative electrode material of Example 3 is 1802.38 mAh g -1 The specific charging capacity of the lithium-ion battery prepared by the lithium-ion battery silicon-carbon composite negative electrode material of Example 4 is 1683.46 mAh g -1 The specific charging capacity of the lithium-ion battery prepared by the lithium-ion battery silicon-carbon composite negative electrode material of Example 5 is 2176.42 mAh g -1 The specific charging capacity of the lithium-ion battery prepared by the lithium-ion battery silicon-carbon composite negative electrode material of Example 6 is 1970.81 mAh g -1 .
[0065] The cycle performance of the lithium-ion battery prepared from the lithium-ion battery silicon-carbon composite negative electrode material of Examples 1 to 6 is shown in the figure below. Figure 4 As shown, at 0.01–1.5V, 1Ag -1Under the current density, the initial capacity of the lithium ion battery prepared by the lithium ion battery silicon-carbon composite negative electrode material of Example 1 is 1516.58 mAh g-1, the charging capacity after 100 cycles is 1210.4 mAh g-1, and the capacity retention rate is 79.81%; the initial capacity of the lithium ion battery prepared by the lithium ion battery silicon-carbon composite negative electrode material of Example 2 is 1439.81 mAh g-1, the charging capacity after 100 cycles is 1199.47 mAh g-1, and the capacity retention rate is 83.31%; the initial capacity of the lithium ion battery prepared by the lithium ion battery silicon-carbon composite negative electrode material of Example 3 is 1046.66 mAh g-1, the charging capacity after 100 cycles is 851.43 mAh g-1, and the capacity retention rate is 81.35%; the initial capacity of the lithium ion battery prepared by the lithium ion battery silicon-carbon composite negative electrode material of Example 4 is 1063.49 mAh g-1, and the charging specific capacity after 100 cycles is 899.02 mAh g-1, and the capacity retention rate is 84.53%; the initial capacity of the lithium ion battery prepared by the lithium ion battery silicon-carbon composite negative electrode material in Example 5 is 1211.76 mAh g-1, and the charging specific capacity after 100 cycles is 1112.03 mAh g-1, and the capacity retention rate is 91.77%; the initial capacity of the lithium ion battery prepared by the lithium ion battery silicon-carbon composite negative electrode material in Example 6 is 1129.71 mAh g-1, and the charging specific capacity after 100 cycles is 959.28 mAh g-1, and the capacity retention rate is 84.91%.
[0066] The XRD patterns of the lithium ion battery silicon-carbon composite negative electrode materials prepared in Comparative Examples 1 and 2 and the negative electrode materials in Comparative Example 3 are shown in FIG. Figure 5 As shown, after XRD analysis, Figure 5 The diffraction peak intensity of the lithium ion battery silicon-carbon composite negative electrode material prepared in Comparative Examples 1 to 2 and the negative electrode material of Comparative Example 3 is relatively high, indicating that its crystallinity is good, and there is no difference from the standard card PDF#27-1402, and it has the characteristic peak of crystalline Si of the cubic crystal system, indicating that the lithium ion battery silicon-carbon composite negative electrode material prepared in Comparative Examples 1 to 2 and the negative electrode material of Comparative Example 3 are crystalline Si phase.
[0067] The charge and discharge curves of the lithium-ion battery prepared from the lithium-ion battery silicon-carbon composite negative electrode materials of Comparative Examples 1 to 3 are as follows: Figure 6 As shown, at 0.01–1.5V, 0.2Ag -1 The specific charge capacity of the lithium-ion battery prepared by the lithium-ion battery silicon-carbon composite negative electrode material of Comparative Example 1 is 840.21 mAh g -1 The specific charging capacity of the lithium-ion battery prepared by the lithium-ion battery silicon-carbon composite negative electrode material of Comparative Example 2 is 1087.82 mAh g -1The charging capacity of the lithium-ion battery prepared by the negative electrode material of Comparative Example 3 is 2608.96 mAh g -1 .
[0068] The cycle performance of the lithium ion battery prepared by the lithium ion battery silicon-carbon composite negative electrode material of Comparative Examples 1-2 and the negative electrode material of Comparative Example 3 is shown in the figure below: Figure 7 As shown, at 0.01–1.5V, 1Ag -1 Under the current density, the initial capacity of the lithium ion battery prepared by the lithium ion battery silicon-carbon composite negative electrode material of comparative example 1 is 850.53mAh g-1, the specific charge capacity after 100 cycles is 773.56mAh g-1, and the capacity retention rate of the lithium ion battery prepared by comparative example 1 after 100 cycles is 90.95%; the initial capacity of the lithium ion battery prepared by the lithium ion battery silicon-carbon composite negative electrode material of comparative example 2 is 926.61mAh g-1, the specific charge capacity after 100 cycles is 292.79mAh g-1, and the capacity retention rate of the lithium ion battery prepared by comparative example 2 after 100 cycles is 31.60%. The initial capacity of the lithium ion battery prepared by the negative electrode material of comparative example 3 is 828.07mAh g-1, the specific charge capacity after 100 cycles is 19.91mAh g-1, and the capacity retention rate of the lithium ion battery prepared by comparative example 3 after 100 cycles is 2.40%.
[0069] The electrochemical test results show that the cycle stability of the embodiments is higher than that of the comparative examples, among which the lithium-ion battery prepared by the lithium-ion battery silicon-carbon composite negative electrode material of Example 2 has the highest charge capacity, which proves that the rigid-flexible synergy of nano-silicon using the rigid three-dimensional porous carbon skeleton and elastic carbon filling has simultaneously improved the charge capacity and cycle stability of the lithium-ion battery. The overall performance tests of Examples 7 to 12 and Comparative Examples 4 to 6 are shown in Table 3.
[0070] Table 3 (Charge specific capacity and discharge specific capacity are obtained from charge and discharge measurements, and cycle stability (capacity retention rate) is obtained from cycle performance tests)
[0071]
[0072] The present invention is described above by way of example. It should be noted that, without departing from the core of the present invention, any simple deformation, modification or other equivalent replacement that can be made by those skilled in the art without inventive effort falls within the protection scope of the present invention.
Claims
1. A lithium-ion battery silicon-carbon composite negative electrode material, characterized in that: include: A rigid three-dimensional porous carbon skeleton, elastic carbon and nano-silicon, wherein the rigid three-dimensional porous carbon skeleton forms three-dimensional pores, and the elastic carbon and nano-silicon are filled in the three-dimensional pores formed by the rigid three-dimensional porous carbon skeleton. The rigid three-dimensional porous carbon skeleton is obtained by carbonizing a polyurethane foam having a through three-dimensional porous structure, and the elastic carbon is obtained by carbonizing a carbon source. In terms of mass fractions, the ratio of the polyurethane foam, the carbon source and the nano-silicon is (1-3):(0.5-1):
1.
2. The lithium-ion battery silicon-carbon composite negative electrode material according to claim 1, characterized in that: The carbon source for forming elastic carbon is citric acid or chitosan.
3. The lithium-ion battery silicon-carbon composite negative electrode material according to claim 1, characterized in that: The pore size of the rigid three-dimensional porous carbon framework is ≤1 micron.
4. A method for preparing a lithium-ion battery silicon-carbon composite negative electrode material, characterized in that: The following steps are involved: Step 1, ball-milling polyurethane foam into particles with a particle size of 5 to 15 microns, dispersing the granular polyurethane foam, carbon source and nano-silicon in a solvent, and mixing until uniform to obtain a first dispersion, wherein the ratio of the granular polyurethane foam, carbon source and nano-silicon is (1 to 3): (0.5 to 1): 1 by mass; Step 2: Dry the first dispersion to obtain a precursor material, calcine the precursor material at 600-800° C. for 2-4 hours in an inert gas atmosphere, and cool it in the furnace to obtain a lithium-ion battery silicon-carbon composite negative electrode material.
5. The preparation method according to claim 4, characterized in that: In step 1, the ratio of nano silicon to solvent is 1:(20-33) by mass.
6. The preparation method according to claim 4, characterized in that: In step 1, the solvent is anhydrous ethanol.
7. The preparation method according to claim 4, characterized in that: The pore size of polyurethane foam is ≤ 1 micron.
8. The preparation method according to claim 4, characterized in that: The particle size of nano silicon is ≤100 nanometers.
9. Use of the lithium-ion battery silicon-carbon composite negative electrode material as claimed in claim 1 in improving the specific charge capacity and / or specific discharge capacity of the lithium-ion battery.
10. Use of the lithium-ion battery silicon-carbon composite negative electrode material as claimed in claim 1 in improving the capacity retention rate of lithium-ion batteries.
Citation Information
Patent Citations
Silicon-carbon negative electrode with three-dimensional integrated conductive network as well as preparation method and application of silicon-carbon negative electrode
CN118763172A
Lithium ion battery silicon-carbon negative electrode material and preparation method thereof
CN118800893A
Silicon carbon composite negative electrode material for lithium ion battery as well as preparation method and applications of material
CN102903896A
Preparation method of Si-C composite negative electrode material of lithium ion battery
CN103000902A
Silicon-containing particle surface elastomer wrapping layer with organic-inorganic interpenetrating network structure and preparation method of silicon-containing particle surface elastomer wrapping layer
CN116779811A
Cited By
Porous carbon material, preparation method thereof and application of porous carbon material in silicon-carbon negative electrode material
CN121528853A
A porous carbon material, a preparation method thereof and application thereof in a silicon-carbon negative electrode material
CN121528853B